Cosmological constraints from H ii starburst galaxy, quasar angular size, and other measurements. Issue 4 (15th November 2021) - Cao, Shulei; Ryan, Joseph; Ratra, Bharat
ABSTRACT: We compare the constraints from two (2019 and 2021) compilations of H ii starburst galaxy (H ii G) data and test the model independence of quasar (QSO) angular size data using six spatially flat and non-flat cosmological models. We find that the new 2021 compilation of H ii G data generally provides tighter constraints and prefers lower values of cosmological parameters than those from the 2019 H ii G data. QSO data by themselves give relatively model-independent constraints on the characteristic linear size, l m, of the QSOs within the sample. We also use Hubble parameter [ H ( z )], baryon acoustic oscillation (BAO), Pantheon Type Ia supernova (SN Ia) apparent magnitude (SN-Pantheon), and DES-3 yr binned SN Ia apparent magnitude (SN-DES) measurements to perform joint analyses with H ii G and QSO angular size data, since their constraints are not mutually inconsistent within the six cosmological models we study. A joint analysis of H ( z ), BAO, SN-Pantheon, SN-DES, QSO, and the newest compilation of H ii G data provides almost model-independent summary estimates of the Hubble constant, H_0=69.7± 1.2 km s^-1 Mpc^-1, the non-relativistic matter density parameter, Ω _m_0=0.293± 0.021, and l m = 10.93 ± 0.25 pc.